2017
DOI: 10.4149/neo_2017_209
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors in plasma cell leukemia treatment: effect of bone marrow microenvironment

Abstract: In the presented study we analysed the effect of histone deacetylase inhibitors (HDACi) suberoylanilide hydroxamic acid (SAHA) and valproic acid (VPA) on human plasma cell leukemia (PCL) cell line UHKT-944 in the presence of bone marrow microenvironment (BMM). For the analysis, the cells were cultured alone, with bone marrow stromal cells (BMSCs), with extracellular matrix (ECM) components or with interleukin-6, and treated with varied concentrations of SAHA and VPA for 24/48 hours. To study the effect of HDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…14 In addition, several studies have shown that HATs and HDACs also (de) acetylate non-histone proteins such as transcription factors, which play an important role in hematopoietic differentiation. [15][16][17][18][19][20][21][22] Given the transcriptional changes associated with neoplastic growth, the use of "epigenetic drugs" has dramatically increased as (adjuvant) treatment of (hematological) malignancies. These drugs include HDAC inhibitors (HDACi) which induce a variety of cellular consequences, including apoptosis, cell cycle arrest, differentiation, and autophagy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In addition, several studies have shown that HATs and HDACs also (de) acetylate non-histone proteins such as transcription factors, which play an important role in hematopoietic differentiation. [15][16][17][18][19][20][21][22] Given the transcriptional changes associated with neoplastic growth, the use of "epigenetic drugs" has dramatically increased as (adjuvant) treatment of (hematological) malignancies. These drugs include HDAC inhibitors (HDACi) which induce a variety of cellular consequences, including apoptosis, cell cycle arrest, differentiation, and autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…This epigenomic modification associates with active regulatory DNA and may influence gene expression by chromatin remodeling and the subsequent recruitment of transcriptional regulators 14 . In addition, several studies have shown that HATs and HDACs also (de)acetylate non‐histone proteins such as transcription factors, which play an important role in hematopoietic differentiation 15–22 …”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation and acetylation are key forms of post-translational modification that regulate the active sites of many proteins [ 5 ]. Some reports have demonstrated that VPA plays an important role in regulating the function of STAT3 by reducing the STAT3 phosphorylation level in biological processes [ 23 25 ]. Unlike the transient STAT3 phosphorylation in normal cells, sustained activation of STAT3 was observed in 70% of blood and solid tumors and showed the strong dependence, which makes it an ideal drug target [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%